Regulatory Perspectives of Pyrrolizidine Alkaloid Contamination in Herbal Medicinal Products - Wiesner, Jacqueline (Planta Medica, 2021)
The toxicity of plants containing certain pyrrolizidine alkaloids has long been recognized in grazing animals and humans. Genotoxicity and carcinogenicity data from in vitro and in vivo (animal) studies were published over the last few decades for some of the 1,2-unsaturated pyrrolizidine alkaloids, leading to regulatory action on herbal medicinal products with pyrrolizidine alkaloid-containing plants more than 30 years ago. In recent years, it has become evident that in addition to herbal medicinal products containing pyrrolizidine alkaloid-containing plants, these products may also contain pyrrolizidine alkaloids without actually including pyrrolizidine alkaloid-containing plants. This is explained by contamination by accessory herbs (weeds). The national competent authorities of the European member states and the European Medicines Agency, in this case, the Committee on Herbal Medicinal Products, reacted to these findings by setting limits for all herbal medicinal products. This review article will briefly discuss the data leading to the establishment of thresholds and the regulatory developments and consequences, as well as the current discussions and research in this area.
Keywords: pyrrolizidine alkaloids; herbal medicinal products; contamination; HMPC